Gene cloning and biochemical characterization of eryngase, a serine aminopeptidase of Pleurotus eryngii belonging to the family S9 peptidases. Issue 11 (2nd November 2014) - Arima, Jiro; Tokai, Shota; Chiba, Masanori; Ichiyanagi, Tsuyoshi; Yabuta, Yukinori; Mori, Nobuhiro; Aimi, Tadanori
Abstract: Pleurotus eryngii serine aminopeptidase that has peptide bond formation activity, redesignated as eryngase, was cloned and expressed. Eryngase has a family S9 peptidase unit in the C-terminal region having a catalytic triad of Ser, Asp, and His. In the phylogenetic relations among the subfamilies of family S9 peptidase (S9A, prolyl oligopeptidase; S9B, dipeptidyl peptidase; S9C, acylaminoacyl peptidase; S9D, glutamyl endopeptidase), eryngase existed alone in the neighbor of S9C subfamily. Mutation of the active site Ser524 of the eryngase with Ala eliminated its catalytic activity. In contrast, S524C mutant maintained low catalytic activity. Investigation of aminolysis activity using l -Phe-NH2 as a substrate showed that S524C mutant exhibited no hydrolysis reaction but synthesized a small amount of l -Phe-l -Phe-NH2 by the catalysis of aminolysis. In contrast, wild-type eryngase hydrolyzed the product of aminolysis l -Phe-l -Phe-NH2 . Results show that the S524C mutant preferentially catalyzed aminolysis when on an l -Phe-NH2 substrate. Graphical abstract: : S524C mutant eryngase (a serine aminopeptidase of Pleurotus eryngii ) preferentially catalyzed peptide bond formation reaction without degradation of the product.